EFFECT OF MIFEPRISTONE AND CABERGOLINE IN THE TERMINATION OF PREGNANCY IN BITCHES - CHAUDHARI, R K; SUTARIA, T V; CHAUDHARI, C F; NAKHASHI, H C; SUTHAR, B N (The Indian Journal of Animal Reproduction, 2022)
Termination of unwanted pregnancy is one of the most common requests from dog owners. Three bitcheswere presented to the clinics with a history that the bitches were mated 30 days back and were diagnosed as pregnant with help of ultrasonography. On the request of owner, pregnancy termination was carried out by using mifepristone @ 2.5mg/kg body weight, orally twice daily with cabergoline @ 5 μg/Kg body weight daily for 4 days. All the three bitches were aborted within 6 days without any side effects.